Metformin Promotes Antitumor Immunity via Endoplasmic-Reticulum-Associated Degradation of PD-L1 - Cha, Jong-Ho; Yang, Wen-Hao; Xia, Weiya; Wei, Yongkun; Chan, Li-Chuan; Lim, Seung-Oe; Li, Chia-Wei; Kim, Taewan; Chang, Shih-Shin; Lee, Heng-Huan; Hsu, Jennifer L.; Wang, Hung-Ling; et al. (Molecular cell, 2018)
Metformin has been reported to possess antitumor activity and maintain high cytotoxic T lymphocyte (CTL) immune surveillance. However, the functions and detailed mechanisms of metformin’s role in cancer immunity are not fully understood. Here, we show that metformin increases CTL activity by reducing the stability and membrane localization of programmed death ligand-1 (PD-L1). Furthermore, we discover that AMP-activated protein kinase (AMPK) activated by metformin directly phosphorylates S195 of PD-L1. S195 phosphorylation induces abnormal PD-L1 glycosylation, resulting in its ER accumulation and ER-associated protein degradation (ERAD). Consistently, tumor tissues from metformin-treated breast cancer patients exhibit reduced PD-L1 levels with AMPK activation. Blocking the inhibitory signal of PD-L1 by metformin enhances CTL activity against cancer cells. Our findings identify a new regulatory mechanism of PD-L1 expression through the ERAD pathway and suggest that the metformin-CTLA4 blockade combination has the potential to increase the efficacy of immunotherapy. [Display omitted] •Metformin enhances antitumor CTL immunity by blocking PD-L1/PD-1 axis•Metformin-activated AMPK directly binds to and phosphorylates PD-L1 at S195•Abnormal PD-L1 glycosylation induced by pS195 leads to PD-L1 degradation by ERAD•Combination therapy with metformin and anti-CTLA4 has a synergistic antitumor effect Cha et al. elucidated a mechanism to show that metformin-activated AMPK phosphorylates PD-L1 at S195 to induce abnormal glycosylation and degrades PD-L1 through an ERAD pathway. This study suggests the potential to use metformin as an adjuvant with various non-PD-L1/PD-1-targeting immune therapies.